Effect of Cold Stretching on Fatigue Properties of Type S31603 Austenitic Stainless Steel at High Temperature. (2015) - Han, Y.; Wang, K.S.
Abstract: Cold stretching of austenitic stainless steel is used to increase its relatively low yield strength by tensile straining at room temperature. Very few studies on the influence of cold stretching for austenitic stainless steels properties are available. This paper focuses on the fatigue behaviors of solution annealed (SA) and cold stretched (CS) S31603 austenitic stainless steel under stress control at 550°C. The results show that the strain amplitude of both SA and CS materials gradually decreases with the development of cyclic deformation until it increases rapidly due to the formation of macrocracks. In all cases, the strain amplitude is smaller in CS conditions compared to that in SA conditions. The longer life cycle of the CS steel is attributed to the smaller strain amplitude, the higher strength, and no α′-martensite formed during cold stretching. The life cycle of CS steel increases with the raised cold stretching level and is roughly characterized by their exponential relationship.